Konsum und Verkehr - Mobilität im Ruckwärtsgang? - Diekmann, Achim (Deutscher Verkehrs-Verl., 2006)
Als Zwischenglied und Endprodukt bildet der Verkehr einen Teil der Produktion und des Verbrauchs von Gütern und Dienstleistungen. Dabei bindet er Ressourcen, teils unmittelbar in den mit der Verkehrserzeugung befassten Bereichen, teils in deren Vorfeld. Seine Bedeutung als wirtschaftlicher Leistungsträger leitet sich aus dem Umfang dieser die Vorleistungsbereiche mit einschließenden Ressourcenbindung ab. Sie findet ihren Ausdruck in der dem Verkehr direkt und indirekt zuzuschreibenden Wertschöpfung. difu

Will consumtion-driven transport continue growth? Transport forms an essential part of private consumption both directly and indirectly. The role it plays reflects both the development of household incomes and the way they are spent. The article identifies the amount of transport services that goes into the production and the final use of goods and services purchased by private households. Using input-output-techniques, it specifies transport intensities of different categories of household expenditure as well as the production sectors involved in satisfying consumer-induced transport demand. One of the main findings of this analysis is that the provison of transport services, including those rendered by the consumers themselves, accounts for about one-fifth of total consumer expenditure. It is against this background that the article investigates the effects consumer behaviour in an ageing society is likely to have on the growth of transport demand in the period up to 2020. difu
Keywords: Verkehr; Mobilität; Dienstleistung; Verkehrsplanung; Verkehrsstatistik; Privater Haushalt; Prognose; Konsum; Verkehrserzeugung; Verkehrsleistung; Wertschöpfung; Wirtschaftsstatistik